2022
DOI: 10.1021/acs.jpcc.1c08561
|View full text |Cite
|
Sign up to set email alerts
|

Forming Platinide Phases under Pressure in the Cs–Pt System

Abstract: A series of platinide-containing phases were identified as thermodynamically favorable compounds at high pressure (10 GPa) using an unbiased automatic crystal structure searching method. Density functional theory paired with a particle swarm optimization (PSO) algorithm supports the formation of Cs2Pt at ambient pressure, agreeing with experimental observations. The calculations then revealed that applying 10 GPa of pressure should result in three new phases: Cs2Pt with the Fe2P-type structure (space group P6̅… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…The MgZn 2 -type structure is a classic representation of the C14 Laves phase (Figure 3a) with two distinct structural units: trigonal-bipyramidal Zn units that share vertices extending into the c-axis, and Mg centering a face-sharing Friauf truncated tetrahedron. 55,56 The literature indicates that Sc can occupy the Mg site and Os can occupy the Zn sites forming ScOs 2 . Prior research has also demonstrated that the Zn sites can accommodate mixed occupancy of transition metal atoms and silicon atoms, resulting in the ordered variant Mg 2 Cu 3 Si-type structure.…”
Section: Ordered Derivatives Of Binary Types: Scos 2 Si 2 and Sc(os 2...mentioning
confidence: 99%
“…The MgZn 2 -type structure is a classic representation of the C14 Laves phase (Figure 3a) with two distinct structural units: trigonal-bipyramidal Zn units that share vertices extending into the c-axis, and Mg centering a face-sharing Friauf truncated tetrahedron. 55,56 The literature indicates that Sc can occupy the Mg site and Os can occupy the Zn sites forming ScOs 2 . Prior research has also demonstrated that the Zn sites can accommodate mixed occupancy of transition metal atoms and silicon atoms, resulting in the ordered variant Mg 2 Cu 3 Si-type structure.…”
Section: Ordered Derivatives Of Binary Types: Scos 2 Si 2 and Sc(os 2...mentioning
confidence: 99%